- Tumblr
- b. [tex](4x-10)^"> b. [tex](4x-10)^" target="_blank">Pinterest
- b. [tex](4x-10)^&body=https://documen.tv/question/use-the-chain-rule-to-find-the-derivative-of-each-of-the-following-a-te-frac-2-3-2-7-3-te-b-te-4-20776695-20/', 'PopupPage', 'height=450,width=500,scrollbars=yes,resizable=yes'); return false" href="#"> b. [tex](4x-10)^&body=https://documen.tv/question/use-the-chain-rule-to-find-the-derivative-of-each-of-the-following-a-te-frac-2-3-2-7-3-te-b-te-4-20776695-20/', 'PopupPage', 'height=450,width=500,scrollbars=yes,resizable=yes'); return false" href="#">Email
Share
Answers ( )
Answer:
see explanation
Step-by-step explanation:
Using the chain rule
Given
y = f(g(x)), then
= f'(g(x)) × g'(x)
(a)
y = = 2 (
= 2. – 3 × (3x² – x + 7)
= – 6 × (6x – 1)
=
—————————————————
(b)
y =
= 10 × (4x – 10)
= 10 × 4
= 40